Modified Lipoproteins Induce Arterial Wall Inflammation During Atherogenesis - Lorey, Martina B.; Öörni, Katariina; Kovanen, Petri T. (Frontiers in Cardiovascular Medicine, 2022)
Circulating apolipoprotein B-containing lipoproteins, notably the low-density lipoproteins, enter the inner layer of the arterial wall, the intima, where a fraction of them is retained and modified by proteases, lipases, and oxidizing agents and enzymes. The modified lipoproteins and various modification products, such as fatty acids, ceramides, lysophospholipids, and oxidized lipids induce inflammatory reactions in the macrophages and the covering endothelial cells, initiating an increased leukocyte diapedesis. Lipolysis of the lipoproteins also induces the formation of cholesterol crystals with strong proinflammatory properties. Modified and aggregated lipoproteins, cholesterol crystals, and lipoproteins isolated from human atherosclerotic lesions, all can activate macrophages and thereby induce the secretion of proinflammatory cytokines, chemokines, and enzymes. The extent of lipoprotein retention, modification, and aggregation show significant person-to-person differences, which have been shown to depend largely on inter-individual differences in the composition of the circulating lipoprotein particles. These properties can be modified by dietary or pharmacological means, and thereby provide opportunities for clinical interventions regarding the prevention and treatment of atherosclerotic vascular diseases.